Analysis of Drainage Capacity in Cimanggis Hill Clove II Housing Area Depok City - Nandiasa, Jantiara Eka; Rizkan, Dega (Journal of Applied Science, Engineering, Technology, and Education, 2019)
Generally, Drainage could be defined as technical measures to reduce excessive water, either from rainwater, permeation, or excessive irrigation water from a region, therefore the land function not disrupted. The purpose of this study are to analyze, learn and evaluate the drain condition and capacity in the Bukit Cengkeh II Residential, Cimanggis Sub-district, Depok City specifically in blockhouse G, H and I to the flood discharge that occurred. The data and information used for this study are primary data (personal research data collected by the author) and secondary data (rainfall from BMKG and nearest Irrigation Center). Flood discharge study methods use two methods, i.e. Rational method and Hasper's method. From these two methods, we used the largest volume of the flood discharge. The results of the Flood discharge planning in block G are 2,39 m3/sec, block H are 5,42 m3/sec, and block I 1,12 m3/sec. There found 10 drains identified as runoff or unsecured. The alternative solutions to runoff or unsecured drains problems are create a new drains dimension plan or construct an infiltration well.